Evaluating the impact of internal control systems on organizational effectiveness at PT Angkasa Pura Indonesia - Yudiantoro, Reza; Nugroho, Bernardus Yuliarto (Institute of Computer Science (IOCS), 2025)
This research aims to analyze the impact of the implementation of internal control systems (ICS) on organizational effectiveness at PT Angkasa Pura Indonesia, focusing on the goal attainment approach in the field of airport services. This research is motivated by the inconsistency between the increase in the Customer Satisfaction Index (CSI) score from ACI World and the number of complaints received by the company. The COSO internal control framework is used as a theoretical foundation to evaluate the implementation of ICS in the company. The empirical analysis results show that the simultaneous implementation of ICS has a significant effect on organizational effectiveness. Specifically, the control environment, information and communication, and monitoring have been proven to have a significant impact on organizational effectiveness, while risk assessment and control activities do not show a significant impact. This study recommends that PT Angkasa Pura Indonesia update its company regulations related to ICS by adopting the latest COSO framework, as well as developing guidelines for internal auditors to evaluate the implementation of ICS effectively. The implication of this research is the importance of focusing on developing ICS elements that have been proven effective in improving organizational effectiveness